Testing Nonlinear Inflation Convergence for the Central African Economic and Monetary Community - Anoruo, Emmanuel; Murthy, Vasudeva N.R. (International Journal of Economics and Financial Issues, 2013)
This paper uses nonlinear unit root testing procedures to examine the issue of inflation convergence for the Central African Economic and Monetary Community (CEMAC) member states including Cameron, Central African Republic, Chad, Equatorial Guinea, Gabon and the Republic of Congo. The results from nonlinear STAR unit root tests suggest that inflation differentials for the sample countries are nonlinear and mean reverting processes. These results provide evidence of inflation convergence among countries within CEMAC. The finding of inflation convergence indicates the feasibility of a common monetary policy and/or inflation targeting regime within CEMAC. Keywords: inflation convergence; STAR; nonlinear unit root tests; inflation differential; CEMAC JEL Classifications: C22; E31; F15; F36